When Right Goes Left: Phantom Touch Induced by Mirror Box Procedure in Healthy Individuals - Ricci, Raffaella; Caldano, Michela; Sabatelli, Ilaria; Cirillo, Emanuele; Gammeri, Roberto; Cesim, Ezgi; Salatino, Adriana; Berti, Anna (Frontiers in Human Neuroscience, 2021)
In the present paper, we investigated the possibility of inducing phantom tactile sensations in healthy individuals similar to those that we observed in patients after stroke. On the basis of previous research, we assumed that manipulating visual feedbacks may guide and influence, under certain conditions, the phenomenal experience of touch. To this aim, we used the Tactile Quadrant Stimulation (TQS) test in which subjects, in the crucial condition, must indicate whether and where they perceive a double tactile stimulation applied simultaneously in different quadrants of the two hands (asymmentrical Double Simultaneous Stimulation trial, Asym-DSS). The task was performed with the left hand out of sight and the right hand reflected in a mirror so that the right hand reflected in the mirror looks like the own left hand. We found that in the Asym-DSS trial, the vision of the right hand reflected in the mirror and stimulated by a tactile stimulus elicited on the left hand the sensation of having been touched in the same quadrant as the right hand. In other words, we found in healthy subjects the same phantom touch effect that we previously found in patients. We interpreted these results as modulation of tactile representation by bottom-up (multisensory integration of stimuli coming from the right real and the right reflected hand) and possibly top-down (body ownership distortion) processing triggered by our experimental setup, unveiling bilateral representation of touch.